Aligning Assessment Practices with Learning Objectives: A Case of EFL Classes in Indonesia - Sri Lestari; Fazri Nur Yusuf (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
The alignment between learning objectives and assessment practices is critical to effective language teaching and learning. This study explores the alignment between learning objectives and assessment practices in English classes at a public senior high school in Jakarta, Indonesia. Grounded in a qualitative case study using Bigg’s constructive alignment framework, the study emphasizes the essential connection among learning objectives, teaching methods, and assessment practices. Involving three selected English teachers, documents comprising lesson plans and assessment instruments, classroom observation, and semi-structured interviews were employed to collect data. Findings indicate that the assessment tasks mostly align with the learning objectives. The assessments focus on the higher level of understanding: extended abstract and relational. However, misalignment between assessment and learning objective is found in this study, based on the missing assessment tasks and incomplete learning objectives stated in the lesson plans. Time constraints, lesson planning issues, and difficulties in designing assessment tasks and rubrics hinder the alignment. It implies that teachers require professional development programs on language assessment literacy and lesson planning, collaborative work with colleagues, and technology integration to maintain alignment, particularly in the context of education reforms. This study contributes to the existing research on constructive alignment in English classroom assessments. It provides insights into how alignment can improve student learning in English classrooms.